ALLOWABLE STRAIN AS AN INDICATOR OF FATIGUE LIFE (Metallurgy and Foundry Engineering, 2011)
Fatigue life, allowable strain and different data on the fatigue resistance of metals and alloys are of great importance for the designer. Knowledge of this subject is very important, given the complicated nature of its impact on many factors, starting with the specific properties of different alloys and in the conditions of their operation ending. This is the reason why, in many cases, the aforementioned complex nature of the effect may remain unknown, which can result in too high values of the safety factors adopted in calculations and, conseąuently, in excessive enlargement of the weight of individual parts of the machinery and equipment, especially as regards the cast elements. In this publication to evaluate the effort (fatigue life), the equivalent strain calculated by the aforementioned method directly from the results of the strain measurements was compared with the permissible strain limit, determined from the results of an MLCF fatigue test. Detailed analysis of the obtained results enables us to claim that permissible strain limit can be regarded as an indicator of the fatigue life.